Planning and managing distributor for Russia's operational environment - Vesterback, Anna (My University, 2012)
This research deals with planning and managing of industrial distributor in Russia’s operational environment. Its objectives are to find out factors that affect distributor’s selection and form selection criteria. A theoretical framework consists of three different groups of factors that are interdependent and have unequal impact on the selection of the distributor. The three groups employed for studying the selection criteria are exporter related factors, operational environment and importer related factors. The features of Russian operational environment, more specifically timber sector are discussed in context of intermediary selection. Further on, the framework is developed for the purpose of the study based on the literature review. As the result, the model for distributor selection is formed. The empirical objectives are to analyze and compare case company’s distributor candidates in Russia using the model from the theoretical part. This is accomplished qualitatively by interviewing 4 potential candidates. Semi-structured interviews were conducted by email and phone. The findings of this research include the list of criteria for selecting the distributor in Russia.
Keywords: distributor selection; selection of intermediary; exporting to Russia; timber trucks; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|